Associated factors with Puerperal Sepsis among Reproductive Age Women in Nandi County, Kenya - Maritim Violet Chepchirchir; Jackim Nyamari; Margaret Keraka (Mashhad University of Medical Sciences, 2017)
Background & aim: Studies have shown that puerperal sepsis is a major cause of maternal morbidity and the second cause of maternal mortality in the developing world. This study aimed to determine the incidence and management of puerperal sepsis among the women of reproductive age (i.e., 15-49 years) attending to two hospitals in Nandi County, Kenya. Methods: This descriptive, cross-sectional study was conducted on 215 women who were diagnosed with puerperal sepsis and referred to two hospitals in Nandi County. Four health care providers in charge of these patients were also included in the study. The sampling was performed using the purposive sampling technique. The data were collected using a structured interview administered by the researcher. Data analysis was performed through SPSS version 20 using the Chi-square test and logistic regression. Results: According to the results of the study, there was a statistically significant relationship between antenatal care attendance and labor duration (OR=0.35, 95% CI: 0.15-0.80). The mothers who had a short labor were 0.35 times more likely to have attended health care facilities to receive antenatal care as compared to those with a long labor. In addition, the food availability showed a significant relationship with duration of labor (OR=5, 95% CI: 1.8-14.28). The mothers with adequate food were five times more likely to experience a short labor compared to those with food shortage. The results also revealed that there was a lack of knowledge on the etiology of infection in the area under investigation. Moreover, the health care facilities were short of the adequate prerequisites to perform puerperal sepsis awareness both in the clinics and community. Conclusion: The findings of the present study underscored the necessity of supplying funds by the Ministry of Health to raise the individuals' awareness on puerperal sepsis and provide them with hygiene education in the investigated area. The integration of hygiene education and puerperal sepsis awareness into antenatal care services should be performed as a strategy to prevent and control the infection.